Oncological diseases and sexuality: Psychological perspective - Enache, Rodica-Gabriela; Ionescu, Lăcrămioara-Mariana; Gherghilescu, Alexandra (Technium Social Sciences Journal, 2022)
In this paper we describe some psychological features of oncological disorders and their impact on emotional and sexual life. We analyzed some case studies of patients from Romania, one of the countries with a high incidence of oncological diseases in women in Europe.